'Mad Girl's Love Song': Reflections on routes into reading, writing and mentoring. Issue 1 (1st December 2016) - Kiernan, Anna
'Mad Girl's Love Song', the title of the poem by Sylvia Plath, forms the starting point of this reflective account because it captures the interdisciplinarity that characterizes my practice and pedagogy, in terms of writing and collaborative working. This article draws on various creative writing methods in response to work by, and projects undertaken with, a range of writers, journalists, musicians and artists. Beginning by re-examining Dorothea Brande's seminal text The Habit of Writing (1981) as a means of identifying the tensions writers often experience between their 'creative' and 'critical' selves, the article concludes that cross-disciplinary working may offer a way of expanding on Brande's notion of these binary selves in favour of a creative/critical/collaborative self.